2020
DOI: 10.1002/adfm.202003207
|View full text |Cite
|
Sign up to set email alerts
|

A Universal Strategy for Tough Adhesion of Wet Soft Material

Abstract: Achieving adhesion between hydrogels and diverse materials in a facile and universal way is challenging. Existing methods rely on special chemical or physical properties of the hydrogel and adherends, which lead to limited applicability and complicated pretreatments. A stitch‐bonding strategy is proposed here by introducing a polymer chain with versatile functional group and triggerable crosslinking property inspired by catechol chemistry. The polymer chain can stitch the hydrogel by forming a network in topol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(107 citation statements)
references
References 55 publications
1
106
0
Order By: Relevance
“…[44][45][46][47] The sphere is made of either optical glass or nickel-coated steel since these surfaces are expected to allow for two common forms of ligand interaction: hydrogen bonding and metal coordination. [27] For our experiments, the spherical probe (radius R = 3.175 mm) is brought into contact with the hydrogel with an initial indentation depth of d ≈ 0.2 mm (which gives an indentation radius of a ≈ 1 mm), left in contact for 30 s (i.e., the dwell time), and then retracted until detachment. The average sample thickness is h 0 ≈ 2.7 mm, which gives an indentation depth to thickness ratio of d/h 0 ≈ 0.1 and a contact radius to thickness ratio of a/h 0 ≈ 0.37.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47] The sphere is made of either optical glass or nickel-coated steel since these surfaces are expected to allow for two common forms of ligand interaction: hydrogen bonding and metal coordination. [27] For our experiments, the spherical probe (radius R = 3.175 mm) is brought into contact with the hydrogel with an initial indentation depth of d ≈ 0.2 mm (which gives an indentation radius of a ≈ 1 mm), left in contact for 30 s (i.e., the dwell time), and then retracted until detachment. The average sample thickness is h 0 ≈ 2.7 mm, which gives an indentation depth to thickness ratio of d/h 0 ≈ 0.1 and a contact radius to thickness ratio of a/h 0 ≈ 0.37.…”
Section: Resultsmentioning
confidence: 99%
“…[4,[23][24][25] For example, DOPA ligands are known to bind to different surfaces through metal-coordination, hydrogen bonding, pi-stacking, and hydrophobic associations. [26,27] It has also been demonstrated that the introduction of pendant DOPA ligands on polymer network backbones increase adhesion to metal-oxide surfaces, [4,14,18,[28][29][30][31] where enhancements in adhesion are the result of these transient interactions acting across interfaces. [4,8,[32][33][34][35][36] Further, the adhesion between two surfaces grafted with DOPA-functionalized brushes can also increase in the presence of metal ions due to ligand bridging.…”
mentioning
confidence: 99%
“…The polished Al coating has a smooth surface and it is easier to form a stable and uniform oxide film, so its anti-corrosion performance is higher than Al coating (Ref 48). Compared with the previous research (Ref [23][24][25] on the hydrogel coatings prepared by chemical methods, the arc spraying method does not require complex reagents and strict reaction conditions, and more importantly, the arc spraying technique has great advantages in terms of cost efficiency and large-scale fabrication.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of PNIPAAm/Chitosan Hydrogel. The synthesis procedure of the hydrogel is similar as described in our previous work (40). NIPAAM (11.22 g) and chitosan (2 g) were first added in deionized water (100 mL), and the pH was adjusted to 5 by dripping HCl solution with a pH meter (Mettler Toledo SevenEasy Series Meters).…”
Section: Methodsmentioning
confidence: 99%